Antisense of survivin inhibits cervical cancer growth in mice - Xu, Hui (Arch Med Sci, 2019)
INTRODUCTION: It is proposed that survivin plays a critical role in the pathogenesis of cancer. Immune regulatory cells are associated with the growth of cancer in the body. Antisenses for the key molecules can suppress tumor growth. This study tests the hypothesis that the antisense of survivin can inhibit cervical cancer. RESULTS: The results showed that human cervical cancer cells expressed high levels of survivin. The levels of survivin in cervical cancer positively correlated with the frequency of interleukin (IL)-10-producing B cells (B10 cells) in the cancer tissue. Survivin increased the expression of IL-10 in B cells. Exposure to survivin antisense efficiently decreased IL-10 expression in B cells. Administration of antisense of survivin inhibited cervical cancer growth and reduced the frequency of B10 cells in tumor-bearing mice. CONCLUSIONS: The results suggest that the survivin antisense has the potential to be used in the treatment of cervical cancer.